Redesign and Implementation of the Electromagnetism Course for Engineering Students Using the Backward Design Methodology - González, Jesús; Martínez, Liliana; Aguas, Roberto; De La Hoz, Jhon; Sánchez, Henry (Sustainability, 2023)
In this study, the redesign and implementation of an electromagnetism course for engineering students are presented using the methodology of backward design (BD), recognized for its attributes for the development of active learning and its possibility of specifying the fundamentals and principles of engineering education in the development of higher education syllabus. The purposes of this study were as follows: (1) to implement the backward design (BD) methodology to develop argumentative, purposeful, and interpretive skills in an electromagnetism course; (2) to design and apply rubrics to evaluate tests and laboratory reports and determine the level that best suits the knowledge, skills, and competencies of students; (3) to assess the perception of students regarding the use of the methodology and their contributions to the development and understanding of the concepts of the course. The results of this educational research experience showed that the BD teaching approach was pedagogical and significantly superior to conventional models for improving knowledge and skills of electromagnetism based on Hake’s statistic (h) of 0.73, which led us to conclude that there was a learning gain in the students. This paper focuses on Sustainable Development Goal 4 (SDG 4) of the United Nations Agenda, which is aimed at “Quality education”. The study’s results reveal that fully integrated and sustainable solutions can be envisioned for higher education entities via the implementation of BD methodology, which can support the educational transformation of the higher education sector based on SDG 4, which promotes inclusive and equitable quality education for all. This can mitigate the risk associated with university dropouts due to subjects that are highly complex for many students like electromagnetism.